"I Know There's Something Like That in Spanish": Heritage Language Learners' Multifaceted Interactions with Linguistically Diverse Peers. (9th September 2020) - Martin‐Beltrán, Melinda; García, Andrés A.; Montoya‐Ávila, Angélica
Abstract : This study contributes to research on heritage language learners (HLLs) and peer interaction by exploring the nature of the interactions between HLLs and their linguistically diverse peers, who may defy traditionally discrete language learner categories. Grounded in sociocultural theory, we analyzed video‐recorded peer interactions during Spanish/English literacy activities in an extracurricular, bilingual secondary program. We found that students' interaction patterns and perceived expertise may shift with different interlocutors and language‐related episodes (LREs). Our findings call for future research to refine the conceptual framing and theorizing of peer interactions, especially involving HLLs across an array of peer groupings. We offer implications for educators mediating peer collaboration and incorporating HLLs' multifaceted linguistic expertise to enhance learning opportunities for diverse learners. Abstract : Este estudio contribuye a las investigaciones sobre los estudiantes de lenguas heredadas y la interacción entre compañeros al explorar el carácter de las interacciones entre estudiantes de lenguas heredadas y sus compañeros lingüísticamente diversos, los cuales no siempre encajan en las categorías delimitadas y tradicionales de estudiantes. Basados en la teoría sociocultural, analizamos videograbaciones de interacciones entre pares durante actividades de escritura en español e inglés, como parte de un programa extracurricular bilingüe a nivel secundario. Hallamos que los patrones de interacción de los estudiantes y sus percepciones sobre la competencia (propia y ajena) pueden variar dependiendo del interlocutor y/o las características del episodio relacionado con la lengua (ERL). Nuestros hallazgos requieren investigaciones adicionales para refinar el marco conceptual y la teorización de las interacciones entre pares, especialmente aquellas que involucran a estudiantes de lenguas heredadas en múltiples agrupaciones de pares. Ofrecemos implicaciones para los docentes que median en la colaboración entre pares e incorporan la competencia lingüística multifacética de los estudiantes de lenguas heredadas para mejorar las oportunidades de aprendizaje de los alumnos diversos.